Quantum Hospitality in The Development of Tourism Village Products in Gianyar, Bali - Ni Desak Made Santi Diwyarthi Santi Diwyarthi; Nyoman Gede Mas Wiartha; Fakhri Fakhrur Rozi; I Wayan Jata; Ardhana Reswari Masykuri (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The development of tourism villages in Bali increasingly requires innovative and adaptive approaches that go beyond conventional service management. In the era of experience economy, community-based tourism, and sustainable destination branding, the concept of Quantum Hospitality emerges as a transformative framework that integrates emotional intelligence, cultural authenticity, local participation, and holistic visitor experience into the development of tourism village products. This study aims to examine the role of Quantum Hospitality in strengthening tourism village products, particularly in the context of Gianyar, Bali, as one of the regions with strong cultural tourism potential. This approach is considered appropriate as it allows for an in-depth understanding of social phenomena, community behavior, and experiential transformation within the tourism village context. Data were collected through in-depth interviews, participant observation, and documentation analysis. The primary method used in this study is in-depth interviews, aimed at capturing the lived experiences, perceptions, and emotional awareness of local stakeholders. Total of 10 informants were selected using purposive sampling, consisting of tourism village community, local MSME actors, culinary business owners, community members involved in tourism services. The findings indicate that Quantum Hospitality contributes to tourism village product development through five main dimensions: emotional resonance, cultural embeddedness, co-creative interaction, symbolic service value, and community-based transformation. These dimensions enable tourism villages to design products that are not only marketable but also meaningful, memorable, and aligned with local wisdom. The study also highlights that the implementation of Quantum Hospitality in tourism villages requires synergy among local communities, tourism managers, government, educational institutions, and digital promotion actors. This paper concludes that Quantum Hospitality offers a relevant and innovative paradigm for strengthening tourism village competitiveness while preserving Balinese cultural identity and promoting sustainable rural tourism development.